Herpetology an introductory biology of amphibians and reptiles - Vitt, Laurie J.; Caldwell, Janalee P. (Academic Press, 2013)
"The fourth edition of the textbook Herpetology covers the basic biology of amphibians and reptiles, with updates in nearly every conceptual area. Not only does it serve as a solid foundation for modern herpetology courses, but it is also relevant to courses in ecology, behavior, evolution, systematics, and morphology. Examples taken from amphibians and reptiles throughout the world make this book a useful herpetology textbook in several countries. Naturalists, amateur herpetologists, herpetoculturists, zoo professionals, and many others will find this book readable and full of relevant natural history and distributional information. Amphibians and reptiles have assumed a central role in research because of the diversity of ecological, physiological, morphological, behavioral, and evolutionary patterns they exhibit. This fully revised edition brings the latest research to the reader, ranging over topics in evolution, reproduction, behavior and more, allowing students and professionals to keep current with a quickly moving field."